2016
DOI: 10.1016/j.ijsu.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of acute diverticulitis severity: A systematic review

Abstract: A number of predictors exist for identifying severe diverticulitis, and CT remains the gold standard for diagnosing complicated disease. Patients who present with identified risk factors for severe disease warrant early imaging, closer in-patient observation and a lower threshold for early surgical intervention. Patients without these factors may be suitable for outpatient-based treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 36 publications
3
30
4
4
Order By: Relevance
“…Four studies reported on CRP level as a risk factor for complicated diverticulitis [ 15 , 16 , 18 , 20 ]. All studies found a significant effect of CRP level on the risk of complicated diverticulitis.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported on CRP level as a risk factor for complicated diverticulitis [ 15 , 16 , 18 , 20 ]. All studies found a significant effect of CRP level on the risk of complicated diverticulitis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a meta-analysis of 23 studies of patients with clinical suspicion for acute appendicitis, the pooled sensitivity of leukocytosis for the diagnosis of acute appendicitis was 0.79 (95% confidence interval 0.78 to 0.81) and pooled specificity was 0.55 (0.54 to 0.57) 88. In a recent systematic review including five studies on the diagnostic value of WBC in acute diverticulitis, WBC could not be reliably used to predict the severity of acute diverticulitis or the need for surgery 89. Similarly, available data suggest that leukocytosis is not sufficiently specific to be used to differentiate bowel strangulation or mesenteric ischemia from other causes of acute abdominal pain 52536566749091.…”
Section: Laboratory Measuresmentioning
confidence: 99%
“…Not only immunocompromised status, but also various underlying disorders have been proposed as a predictive factor of severity. 17 However, we evaluated only immunocompromised status, including glucocorticoid in this study. We note that our study exclusively evaluated patients with ACD.…”
Section: Discussionmentioning
confidence: 99%
“…16 According to the previously reported predictors of severe diverticulitis, we also reviewed the use of non-steroidal antiinflammatory drugs, past episodes of diverticulitis, and serum Creactive protein for adjustment of confounding due to severity. 17 We also evaluated blood culture results if submitted.…”
Section: Study Variablesmentioning
confidence: 99%